2017
DOI: 10.1128/aem.02615-16
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Protein Sources in the Diet Modulate Microbiota and Functionality in the Distal Intestine of Atlantic Salmon (Salmo salar)

Abstract: The present study aimed to investigate whether alternative dietary protein sources modulate the microbial communities in the distal intestine (DI) of Atlantic salmon, and whether alterations in microbiota profiles are reflected in modifications in host intestinal function and health status. A 48-day feeding trial was conducted, in which groups of fish received one of five diets: a reference diet in which fishmeal (diet FM) was the only protein source and four experimental diets with commercially relevant compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
165
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(209 citation statements)
references
References 69 publications
39
165
1
Order By: Relevance
“…In addition, the results show that bacterial diversity in the gut content was higher than that in the gut mucosa of rainbow trout, which has been shown previously in Atlantic salmon (Gajardo et al . , ). In contrast, high‐throughput sequencing studies on rainbow trout and Asian seabass have shown no differences in bacterial diversity between gut content and mucosa (Lyons et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the results show that bacterial diversity in the gut content was higher than that in the gut mucosa of rainbow trout, which has been shown previously in Atlantic salmon (Gajardo et al . , ). In contrast, high‐throughput sequencing studies on rainbow trout and Asian seabass have shown no differences in bacterial diversity between gut content and mucosa (Lyons et al .…”
Section: Discussionmentioning
confidence: 99%
“…) and Atlantic salmon (Gajardo et al . ) fed diets with higher inclusion levels of FM. Similarly, the present study found higher abundances of Photobacterium in the FM diets and in the gut content of fish fed FM, at least in cold water (Figs and ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the PI showed presence of Spirochaetes that were not found in the MI showing that metagenomics can be used to identify microbial communities that inhabit diferent segments of the gut. In another study, Gajardo et al [11] identiied bacterial groups associated with diet-induced gut dysfunction that could serve as biological markers of the gut health status in Atlantic salmon. Mouchet et al [73] compared the gut microbiota of 15 ish species from the Atlantic Ocean near Brazil and showed that the microbiota genetic diversity was highly inluenced by the ish species, geographical location and diet.…”
Section: Gut Mucosal Microbiotamentioning
confidence: 99%
“…In terms of assembly, both whole genome shotgun and marker gene guided sequencing have been used on diferent aquatic organisms. The commonly used marker gene in metagenomics analyses is the 16S ribosomal RNA (16S rRNA), which has been widely used to characterize the microbiota of diferent aquatic organisms including rainbow trout [88,89], Atlantic salmon [11,12], turbot (Scophthalmus maximus) [90], lamprey (Lampetra morii) [91] and Baleen whale [92]. Whole genome shotgun sequencing has also been widely used in the study of environmental microbial communities and pathogens infecting diferent aquatic organisms.…”
Section: Metagenomics Technologies and Their Limitationsmentioning
confidence: 99%
See 1 more Smart Citation